Analysis and Prediction of Stable Height of Capillary Water Rising under Unsaturated Subgrade Soil - Jianfeng Cao; Zhihao Mao; Liqiang Hu; Yunfei Dai; Yu Luo; Wenwei Zhou (Advances in Civil Engineering)
In order to study the capillary water height of the highway subgrade and balanced moisture condition of the subgrade affected by groundwater, the standpipe method has been used in this study to track the measured data. It involves the analysis of the factors affecting the capillary water stability height of the coarse-grained soil and fine-grained soil filler as well as establishing the corresponding prediction model. The comparative analysis with the experimental tracking results and related literature shows that the prediction model developed in this study is highly accurate and can be applied for the analysis of the balanced moisture condition of the highway subgrade.